Regulation of cell signalling by iRhoms - Sieber, B (2019)
My first project focuses upon the regulation of TACE by oncogenic stimulation. TACE (for TNFα-activating enzyme) is a major regulator of numerous cell signalling pathways, including epidermal growth factor receptor (EGFR) signalling. TACE acts at the plasma membrane to release signalling factors into the extracellular medium. iRhom1 and iRhom2 are multi-pass membrane proteins that belong to the rhomboid-like superfamily, and they are the ultimate regulators of TACE activity. It has been recently discovered that the phosphorylation of iRhom2 is required for the stimulated activity of TACE at the plasma membrane. However, whether iRhom phosphorylation is crucial in other pathological contexts is unknown. In addition, the role of iRhom1 phosphorylation in TACE activation remains unstudied.